Association between post-dialysis hemoglobin level and the survival of vascular access. Issue 1 (January 2018) - Nishiwaki, Hiroki; Hasegawa, Takeshi; Ikenoue, Tatsuyoshi; Tominaga, Naoto; Yazawa, Masahiko; Kawarazaki, Hiroo; Shibagaki, Yugo; Yamamoto, Yosuke; Fukuma, Shingo; Yamazaki, Shin; Fukuhara, Shunichi
Introduction: Although a few dialysis facilities conduct a complete blood cell count for some patients at post-dialysis, including hemoglobin, clinical findings supporting the interpretation of results are scarce. The aim of this study was to investigate the association between post-dialysis hemoglobin level and vascular access failure with clinical data. Methods: Study design : Case crossover design. Setting : Japanese dialysis facilities, which routinely take post-dialysis blood samples, including complete blood cell counts at least once a month. Participants : Hemodialysis patients who experienced vascular access failure in January 2010 until December 2014. Exposure : Post-dialysis hemoglobin level. Main outcome : Vascular access failure treated with endovascular treatment or operation. Statistical analysis : Self-matched odds ratios and 95% confidence intervals were estimated by comparing post-dialysis hemoglobin just before events ("case") with levels at 6 and 12 months before events ("control") using conditional logistic regression, and presented with restricted cubic spline. Results: Two hundred and thirty hemodialysis patients with vascular access failure were identified. Mean post-dialysis hemoglobin level before the failure was 11.8 g/dL (standard deviation 1.7). The spline curve showed that higher post-dialysis hemoglobin levels above 11.8 g/dL had a greater odds ratio for vascular access failure. Post-dialysis hemoglobin levels and odds ratios (95% confidence interval) for vascular access failure relative to the reference value (Hb 11.8 g/dL) were Hb 12.0 g/dL, 1.1 (1.0-1.1); Hb 14.0 g/dL, 1.4 (1.0-2.0); and Hb 16.0 g/dL, 2.1 (1.1-4.3). Conclusions: A higher post-dialysis hemoglobin level was associated with vascular access failure. Higher post-dialysis Hb could be a factor that triggers vascular access failure.